Một số chế độ, chính sách cưa nhà nươc trong tinh hinh moi (Vietnamese law coll. (Harvard Law School), 1967)
Collection of decisions, circulars, instructions on manpower, workers' benefits, working conditions, military service and financial administration in the new mobilization for war.